The influence of Magnesium on the athletic performance - Vasilescu, M. M.; Dragimir, M.; Rusu, L. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
. In the present it is admitted that any tissue is capable of producing IGF-I. The increase in IGF - I can contribute to the hypertrophic response of skeletal muscle through direct stimulation of the proteic synthesis and the multiplication of the satellite cells (anabolic effect and myogenic). Zn and Mg facilitates the action of anabolical factors. The decrease in serum concentration of Zn and Mg are amplified by the prolonged physical effort and/or by high velocity. The B6 vitamin besides the known anabolic effect increase the absorption of Mg and Zn. Objectives Our study was purpose to examine the effects of the administration of Zn -Mg -B6complex has on the isometric muscular contraction. Methods Twenty athletes have been used ( V= 18 + 2 years, T = 178 + 3,5cm ; G = 70 + 2,5 kg ), greco - roman wrestlers and athletics practisers, divided in group A - for research purposes (n=10) and group B - witness (n=10). For ten weeks, at sleep hours, in a single oral doze it has been administrated Zn (30 mg), Mg (450 mg) and B6(10 mg) (following the Brilla and Conte method, 2ooo ) to the research group A, and the placebo effect to the witness group B. Initially and after the end of the administration tests have been run to observe the isometric muscular contraction of the hand grip type with the help of a hand - dynamometer TSD 121 C connected to a collecting and data analyzing system BIOPAC MP 150 PC. Results From the data obtained from the two groups of subjects we observe at the end of the study an improvement of the initial maximum contraction (Cmi) with 13,24 % at the study group in reference to the 8,33 % of the witness group, and also 14,37 % to the previous 9,8 % at the final maximum contraction (Cmf) (F1,F2). Conclusion The administration of the Zn-Mg-B6vitamin complex can contribute to the augmentation of the muscle force.